Artists and urban space: the representation of the city in contemporary art - Chaves Martín, Miguel Ángel (Historia y Comunicación Social, 2014)
In this construction of the image of the modern city, besides the public art will, it also play an important role the area of representations of the city, both in painting and photography or graphic illustration. These differing viewpoints to the cityscapes, critical or creative, objective or perceived, reveal the contradictions of the modern city, their values, meanings, at the time that have an influence on the appreciation of the citizens as spectators have of them, who analyzed and see the city from its plastic images.